Analisis Strategi Pengelolaan Sagu Untuk Mendukung Ketahanan Pangan di Kabupaten Mimika - Fonataba, Mirandolla Mariolin; Sandy, Stepanus (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze sago management strategies in supporting food security in Mimika Regency. Local food security still faces various challenges, particularly the high dependence on rice and the underutilization of local food resources. Sago is a local food commodity with high economic, social, and ecological value; however, its management has not been optimized. This study employed a descriptive approach using SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats). Data were collected through observation, interviews, and questionnaires administered to 50 respondents, including local communities, sago processors, customary institutions, and officials from the Mimika Regency Agriculture Office. The results indicate that strengths and opportunities outweigh weaknesses and threats, placing the strategy in Quadrant I (aggressive strategy). The recommended strategy is to leverage internal strengths to seize external opportunities through community capacity building, optimization of sago land utilization, development of sago-based processed products, and strengthening collaboration among stakeholders.